HUBUNGAN ANTARA FEAR OF MISSING OUT DENGAN SUBJECTIVE WELL BEING PADA REMAJA PENGGUNA INSTAGRAM - Nur Rama Yuniani; Arif Tri Setyanto; Rosita Yuniati (Jurnal Psikohumanika, 2021)
ABSTRACT Instagram is the highest media social which accessed by teenagers in the development of information technology nowadays. The excessive use of Instagram creates the Fear of Missing Out phenomena which can reduce life satisfaction, bring up negative moods, create someone feels insufficient and compare themselves with others. Therefore, Fear of Missing Out affects the Subjective Well Being This study aims to find out the correlation between Fear of Missing Out and Subjective Well Being among teenagers Instagram’s users. The hypothesis proposed in this study is Fear of Missing out and Subjective Well Being among teenagers Instagram’s users. This study uses a quantitative method and proportionate stratified random sampling technique for getting the samples. The subjects in this study were 129 students of SMA Negeri 7 Surakarta which are Instagram’s users between 15-18 years old. The measuring instruments used in this study are the Fear of Missing Out scale and Subjective Well Being scale. The data analysis used is Karl Pearson’s Product Moment correlation in SPSS 21.0 for Windows release. The analysis showed a correlation coefficient rxy= -0,209 with P=0,019 (p<0.05). It proves there is a significant negative relationship between Fear of Missing Out and Subjective Well Being. Therefore, the hypothesis proposed in this research is accepted. Rsquare value of 0,044 means that Fear of Missing Out gives effective contribution of 4,4% to Subjective Well Being. Keywords: Fear of Missing Out, Subjective Well Being, Teenager, Instagram.